The Effect of Health Coaching on the Community's Availability to Vaccinate - Nur Isriani Najamuddin; Masyita Wahab; Hadryani Amin; Andi Marsida (Jurnal Vocational Nursing Sciences (VNUS), 2021)
Background: The number of negative issues regarding COVID-19 affects the public's perception of not participating in the COVID-19 vaccination. Based on a brief interview conducted by the researcher with 20 people in the Matangnga Health Center working area regarding the implementation of vaccination, 17 people expressed their doubts and were not willing to vaccinate. Because in this study, what needs to be changed is the public's perception of the COVID-19 vaccination, the health education method that will be used is the health coaching method. Objective: To determine the effect of providing health coaching on people's willingness to vaccinate in the work area of the Matangnga Health Center, Polewali Mandar Regency. Methods: The research design used was experimental research with a one-group pretest-posttest research design. Population In the study, namely all people over the age of 18 years, amounting to 3,444 people with a sample of 20 respondents, Sampling was done using the multistage sampling technique. The data collection tool used in this study was a questionnaire consisting of 17 statement items. Results: The normality test of the data using the Saphiro Wilk test showed that the data was normally distributed, and then the data was analyzed using the paired t test with the results of the p value of 0.000 <0.05. Conclusion: The results of the analysis of community attitudes towards the implementation of vaccination before and after the provision of health coaching showed that there was an effect of providing health coaching on the community's willingness to vaccinate in the work area of the Matangnga Health Center, Polewali Mandar Regency. Suggestion: It is hoped that this health coaching intervention can be developed further and can be used as a method for providing health education.